Differential pressure sensor using flexible piezoelectrics with pyroelectric compensation. (5th February 2021) - Ramanathan, Arun K; Headings, Leon M; Dapino, Marcelo J
Abstract: Polyvinylidene fluoride (PVDF) is a mechanically tough, low density piezoelectric polymer commercially available as a flexible film that can be conformed to arbitrarily-shaped surfaces using simple adhesive bonding. A fundamental challenge that prevents the implementation of piezoelectric sensors for pressure sensing applications is their inability to measure static or very low frequency signals. Further, due to their large pyroelectric constants, they are limited to measurements where the rate of change in temperature is smaller than the lower cutoff frequency of the system. Under steady flow conditions, the cantilever unimorph possesses the highest sensitivity compared to other conventional configurations such as compression, doubly clamped unimorphs, or diaphragms. However, to preserve the overall noninvasive nature and linearity of the sensor, it is necessary to optimize the geometry and material properties in order to maximize charge output while minimizing deflection. To address these challenges, this work focuses on the development of a cantilever PVDF unimorph for static differential pressure measurement with pyroelectric compensation. A design optimization procedure to maximize the charge sensitivity of a cantilever unimorph is presented and the optimized cantilever is interfaced with a large-time-constant, drift-compensated charge amplifier for near-static pressure measurements. Voltage error due to temperature changes accompanying the input flow is compensated using a compressive mode sensor and an empirical compensation algorithm. Within the investigated range, the sensitivity of the fabricated sensor is 1.05 mV Pa −1 with an average resolution of 10 Pa and 97.3% linearity.